Chronic toxicity of Cadmium and its effects on activity of TGO, TGP, creatinine and histological alteration in kidney and liver in Rattus norvegicus variety SPRAGUE DAWLEY. - Henry Díaz-Murillo (2019)
Cadmium effects on body weight, the activity of AST, ALT, and creatinine histological changes in the liver and testis Sprague Dawley Rattus norvegicus was evaluated. The experimental evaluation was performed at the Laboratory of Animal Physiology of the Academic Department of Biology of the UNSA Arequipa, during the months of January to June 2015. Control (Distilled water), Group 2 (5 mg / kg of cadmium chloride), Group 3 (. 10 mg / kg of cadmium chloride) and Group 4 (20: 24 Sprague Dawley Rattus norvegicus allocated in four treatment groups mg / Kg. of cadmium chloride) for 4 weeks. It significant difference (p <0.05) was found in body weight of rats in different groups of evaluation. When applying postcomparación Tukey test it was found that in the treatment with cadmium chloride at doses of 20 mg / kg / day, body weights of rats treated decreased significantly. It significant difference (p <0.01) was observed in the activity of SGOT, SGPT creatinine of rats in different groups of evaluation. When applying postcomparación Tukey test revealed that in treatments with cadmium chloride at doses of 10 and 20 mg / kg / day levels of GOT, GPT and creatinine intoxicated rats increased significantly. Chronic exposure to cadmium chloride caused congestion with mild hepatic sinusoidal dilation and alteration of architectural arrangement of hepatocytes; vascular congestion and increased glomerular cellularity of moderate to severe hyaline degeneration of tubular epithelium in rats that were administered cadmium chloride at doses of 10, 20 mg / kg / day for 30 days.